Assessing the ecosystem health of Ratargul Freshwater Swamp Forest in Bangladesh using a modified forest quality index - Md. Sahinur Islam Fahim; Md. Shydul Amin; Md. Shamim Reza Saimun; Wahidur Rahman; Sohag Ahammed; Monwar Hossain; Fahmida Sultana; Sharif A. Mukul; Mohammed Abu Sayed Arfin-Khan (Ecological Indicators, 2025)
Freshwater swamp forests are globally vulnerable ecosystems, facing significant degradation threats that compromise their ecological health. Understanding the current state of these imperiled ecosystems and the factors affecting their quality is vital for targeted conservation and management. The present study assessed the ecosystem health of the Ratargul Freshwater Swamp Forest (RFWSF), the only remaining freshwater swamp forest in Bangladesh. We developed a modified Forest Quality Index (FQI) to evaluate RFWSF’s ecosystem health by integrating five key components: biotic integrity, soil quality, water quality, socio-economic conditions, and ecotourism value. Each component was quantitatively assessed using corresponding indices—the Forest Biotic Integrity Index (FBII), Forest Soil Index (FSI), Forest Water Index (FWI), Forest Socioeconomic Index (FSEI), and Forest Ecotourism Index (FEI). Sixty randomly selected plots were established across three forest classes, based on canopy density: high dense forest (HD), moderate to low dense forest (MD), and low to no forest (LD). Principal Component Analysis (PCA) was used to identify key variables contributing to the overall FQI. The FQI was categorized into five levels: 1 (Worst), 2 (Bad), 3 (Moderate), 4 (Good), and 5 (Excellent). Our findings indicate that all components were of moderate quality (FQI = 3) in both HD and MD areas, except for the FSEI, which was of poor quality (FQI = 2). The LD areas exhibited poor overall ecosystem health (FQI = 2), primarily due to reduced biotic and soil quality. Although water quality was significantly lower (p < 0.05) in HD and ecotourism zones, no significant difference in overall ecosystem health was observed between ecotourism and non-ecotourism zones. The mean Normalized Difference Vegetation Index (NDVI) values were 0.48, 0.49, and 0.41, respectively, for HD, MD, and LD areas, aligning with the observed FQI trends. Spatial analysis of ecosystem health hotspots revealed good to excellent conditions concentrated in the central part of RFWSF, with degradation prevalent along its edges. Overall, our study finds RFWSF in a moderately healthy state and offers a component-based framework to guide site-specific conservation and sustainable management of similar wetland forest ecosystems.